Sosialisasi Program Studi Penerangan Aeronautika Di SMA Negeri 3 Kabupaten Tangerang - Arti, Endang Sugih; Amir, Elfi; Wagini, Dini; Maruli, Togi Adnan; Cahyono, Ferry Budi; Agustono, Agustono; Sadiatmi, Rini (Jurnal Pengabdian Kepada Masyarakat, 2024)
Based on Law No. 20 of 2003, Article 1, regarding the national education system, it is stated that education should be conducted democratically, fairly, and without discrimination, while upholding human rights, religious values, cultural values, and the diversity of the nation. Additionally, Presidential Regulation No. 68 of 2022 concerning the Revitalization of Vocational Education and Vocational Training is also relevant.In light of these two regulations, there is a need for information about higher education institutions that can meet the criteria outlined in these regulations. Furthermore, there is a need for information about higher education institutions that are easily accessible, have relatively affordable tuition fees, offer relatively short education durations to facilitate quick graduation, and prepare students for the workforce by equipping them with practical skills during their education at PPI Curug, a vocational higher education institution. The proposed solution is to provide students of SMAN 3 with an understanding of the importance of acquiring competencies and skills to be job-ready through the dissemination of knowledge during socialization sessions. This will help students realize the value of applying the knowledge they gain at PPI Curug in their future careers. This Community Engagement Program (PKM) aims to introduce the Diploma III Program in Aeronautical Information Services, whose graduates will work in the field of aviation, providing flight information in the form of self-briefings, Notice To Airmen (NOTAM), Aeronautical Information Publications (AIP), and aeronautical charts/maps. It is hoped that through this explanation, PKM participants will be motivated and develop an interest in continuing their education at PPI Curug, especially in the Diploma III Program in Aeronautical Information Services. The activities have progressed smoothly, and there is a high level of interest among students from SMAN 3 Kabupaten Tangerang, as evidenced by the numerous questions raised during the sessions.